The influence of side-lying position on oropharyngeal swallow function in at-risk infants: an exploratory study - Smith, Julian B.; Kamarunas, Erin; O’Donoghue, Cynthia (Clinical Pediatrics, 2023)
This investigation assessed the effect of side-lying position on infant oropharyngeal swallow physiology. Infant modified barium swallow studies (MBS) recordings were retrospectively examined in matched-pairs comparing at-risk infants swallowing in both an upright/cradled position and a side-lying position. Swallow parameters were measured independently and through a consensus coding approach. Infants fed in side-lying position showed a decrease in airway invasion severity as compared with when those same infants were fed in an upright/cradled position (P = .009). Bolus location at the time of swallow initiation was higher when infants were fed in side-lying position as compared with cradle position (P = .024), representing decreased risk of airway invasion. Infants fed in side-lying position demonstrated fewer swallows per breaths (P = .032). This pilot study validates the need for additional research to further define the mechanisms related to this improvement, and to determine how diagnosis and medical stability moderate these findings.
Keywords: dept.cmd; peer-reviewed